Características sociodemográficas, clínicas y médicas de hipertensos residentes en los territorios vecinales 06, 09, 10, 35, 36, 49 y 53 del distrito de Trujillo – 2013 - Quispe Daga, Luis Miguel (2014)
We realize a descriptive study of transverse court with the aim to determine which are the characteristics partner demographic, clinics and medical hypertensive residents in neighborhood areas 06, 09, 10, 35, 36, 39, 49 and 53 of the district of. The population consisted of 47 patients, 13 men and 34 women. Home visits were made during the months of August to December 2013 , in which information on a medication history ( Dader method) for each patient , which includes health problems, medications used, blood pressure was measured weight recorded , height, waist circumference and waist / hip ratio . It was found that 44.46 % of patients were within the age range of 70-79 years, by sex 53.85 % for men and 41.18% women. The 40.43 % have higher education degree , 4.26% of patients smoked and 23.4 % of the population consumes alcohol, compared to 48.94 % controlled diet feeding and 23.4 % of patients perform exercise frequently , 51% of the population is overweight and obesity has 29.79% type I and 23% of the population has a moderate risk of a cardiovascular event. The most common disease is hypercholesterolemia with 8.89 % of the population, with 63.83 % of the population have their blood pressure controlled drug group and the most used by 35.85 % of the population are the angiotensin-converting enzyme inhibitors ( ACEI ) being the most representative enalapril